Pelaksanaan Pendidikan Kewirausahaan dalam Program Double Track pada Sekolah Menengah Atas di Kabupaten Banyuwangi - Alfiyah, Nurul; Siska, Astri Iga; Kareja, Novilia (Universitas Pendidikan Ganesha, 2022)
This study focuses on the analysis of the implementation of entrepreneurship education in the double track program in Banyuwangi Regency Senior High Schools that have implemented this program, so that it is expected to be an example for other high schools. The study used descriptive qualitative methods with research subjects namely SMAN 1 Purwoharjo and SMAS 1 Muhammadiyah Banyuwangi, including school principals, entrepreneurship teachers and double track program supervisors, as well as students. Data were obtained by means of in-depth and semi-structured interviews, observations, and